Evaluación de la cadena de abastecimiento para el área de mercancías en la empresa Servientrega Ecuador s.a. regional Latacunga. propuesta modificar el sistema de la cadena de abastecimiento en base al estudio de tiempos y movimientos - Pinta Guanoluisa, Wilson Xavier (2016)
The work done had an objective to evaluate the supply chain to improve the delivery of goods within SERVIENTREGA ECUADOR Company S.A. Regional Latacunga; the main problem is generated by the delays caused at the time of unloading the goods from the different local areas, inadequate distribution of the goods in the hold, delay in making deliveries respective goods, lack of knowledge in the work of palletizing within and out of the cellar. It is to be used formative research in as it will evaluate the model of supply chain people when zoning do not have a time control standard for performing, each activity causes inefficiencies in the process, lack knowledge of an appropriate way to aestivate goods cause problems when storing and dispatching trucks merchandise, plus the plant does not have the necessary markings risks, so that workers or employees do not have the visibility of the signals in each area, the delay of delivery of goods by the lost Courier of customers is generated, for this reason and with the proposed improvement in the distribution of goods such customers recover….